2012
DOI: 10.1111/j.1463-1326.2012.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liraglutide versus other incretin‐related anti‐hyperglycaemic agents

Abstract: The two classes of incretin-related therapies, dipeptidyl peptidase-4 (DPP-4) inhibitors and glucagon-like peptide-1 receptor agonists (GLP-1 RAs), have become important treatment options for patients with type 2 diabetes. Sitagliptin, saxagliptin, vildagliptin and linagliptin, the available DPP-4 inhibitors, are oral medications, whereas the GLP-1 RAs-twice-daily exenatide, once-weekly exenatide and once-daily liraglutide-are administered subcutaneously. By influencing levels of GLP-1 receptor stimulation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 90 publications
(145 reference statements)
2
20
0
1
Order By: Relevance
“…Furthermore, 27% of GLP-1 receptor immunoreactive neurons in the duodenum and 79% of these neurons in the colon are co-expressed with nNOS [175] . Due to its promising potential in the treatment of type 2 diabetes and related intestinal motility disorders, the incretin-based therapies have been the focus of much interest during the last years [176][177][178][179] . Incretins, which are released by enteroendocrine cells in the intestine in response to a meal, have been implicated in contributing to the pathogenesis of type 2 diabetes mellitus.…”
Section: New Strategies To Improve Glycemic Control In Diabetesmentioning
confidence: 99%
“…Furthermore, 27% of GLP-1 receptor immunoreactive neurons in the duodenum and 79% of these neurons in the colon are co-expressed with nNOS [175] . Due to its promising potential in the treatment of type 2 diabetes and related intestinal motility disorders, the incretin-based therapies have been the focus of much interest during the last years [176][177][178][179] . Incretins, which are released by enteroendocrine cells in the intestine in response to a meal, have been implicated in contributing to the pathogenesis of type 2 diabetes mellitus.…”
Section: New Strategies To Improve Glycemic Control In Diabetesmentioning
confidence: 99%
“…This review examines the comparisons between two classes of incretin based therapies, dipeptidyl peptidase 4 (DPP-4) inhibitors (incretin enhancers) and glucagon-like peptide 1 (GLP-1) agonists (incretin mimetics). Although use of incretin based therapies for T2DM has been reviewed before [9-11], this article focuses on data from head to head comparative trials analyzing efficacy, tolerability and safety profiles between the agents from these two classes.…”
Section: Introductionmentioning
confidence: 99%
“…In a substudy involving patients from the LEAD-2 and LEAD-3 studies, weight loss was found to correspond to a reduction in visceral and subcutaneous fat (as opposed to lean tissue mass), thus reducing the long-term risk of cardiovascular disease [89]. Weight loss with liraglutide is also discussed elsewhere within this supplement [23,24].The majority of GLP-1 RA-associated side effects are gastrointestinal, with most complaints relating to nausea, particularly early in treatment. Clinical data have revealed that the effect of liraglutide treatment on weight loss, which is generally a more long-term effect than the nausea, was observed irrespective of gastrointestinal adverse effects [90].…”
mentioning
confidence: 97%